Gaya Hidup Frugal Living dalam Penggunaan Qris menurut Pandangan Islam: Frugal Living and QRIS: The Transformation of Financial Modesty in Islam - Yonifia, Ismi; Rahman, Bobbi Aidi (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This research aims to determine and analyze how frugal living can influence a person in determining priorities in life Design/methodology/approach: The writing method used is a descriptive method with an analytical approach to determine the relationship between the use of QRIS technology and the frugal living lifestyle, where data collection techniques rely on references in the literature method as the main source. In other words, the data method collected and obtained from literature such as the Qur'an and scientific journals related to the discussion of QRIS and frugal living. Findings: The results showed that applying a frugal living lifestyle by using QRIS as a payment aid, a person will avoid negative things such as debt and wastefulness. This is in accordance with Islamic teachings where wastefulness and excess are hated by Allah SWT. Research implications: QRIS is one of the latest technologies that can help people who wants to adopt a frugal lifestyle. Using QRIS will enable people to better manage their financial expenses for daily needs.